Delphi technique between the easy theoretic and the difficulty application in scientific research and future studies - Amrouche, Toumia (Technium Social Sciences Journal, 2022)
The application of Delphi technique in scientific studies and future scientific research gave it a great importance according to the efficiency and effectiveness of its results. It is able to find solutions to any research problem by following the methodological steps during its application, starting with the selection of experts and identifying the problem studied carefully to the results or the final report that prepared by the researcher based on the opinions and expert ideas. This technique combines between quantitative and qualitative way. It is based mainly on questionnaires distributed from two to four phases as a maximum, which contain open questions in its first phase and closed ones in the rest of the stages. Through this paper we will try to explain this technique, the steps that are based on it with its advantages, disadvantages and the difficulties of its application with a typical example explaining how to apply them.